Nonparametric Comparative Statics and Stability. - Hale, Douglas (Princeton University Press, 2014)
The authors, leading researchers in the fields of mathematical economics and methodology, present the first comprehensive synthesis of literature on qualitative and other nonparametric techniques, which are important elements of comparative statics and stability analysis in economic theory. The topics covered show how to assess the comparative statics and stability of economic models without a precise quantitative knowledge of all model components. Applications of the analysis range from determining refutable hypotheses from theory to auditing the solutions of large, computer-based systems.
Cover; Contents.
Keywords: Economics, Mathematical.; Macroeconomics -- Mathematical models.; Equilibrium (Economics); Macroéconomie -- Modèles mathématiques.; Mathématiques économiques.; MATHEMATICS -- Probability & Statistics -- General.; BUSINESS & ECONOMICS -- Economics -- General.; BUSINESS & ECONOMICS -- Reference.; Economics, Mathematical; Macroeconomics -- Mathematical models; Electronic books.